2022
DOI: 10.3389/fphar.2022.930470
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Rare DPYD Genetic Polymorphisms for 5-Fluorouracil Therapy in the Japanese Population

Abstract: Dihydropyrimidine dehydrogenase (DPD), encoded by the DPYD gene, is the rate-limiting enzyme in 5-fluorouracil (5-FU) degradation. In Caucasians, four DPYD risk variants are recognized to be responsible for interindividual variations in the development of 5-FU toxicity. However, these risk variants have not been identified in Asian populations. Recently, 41 DPYD allelic variants, including 15 novel single nucleotide variants, were identified in 3,554 Japanese individuals by analyzing their whole-genome sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Several studies have shown a link between reduced DPYD enzyme activity and increasing the risk of severe toxicity. A recent study has reported that the functional alterations of enzyme activities caused by DYPD variants were characterized 21 . The rs200562975of DPYD identified in the present study reportedly reduced enzymatic activity to less than 70% of wild-type in vitro 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown a link between reduced DPYD enzyme activity and increasing the risk of severe toxicity. A recent study has reported that the functional alterations of enzyme activities caused by DYPD variants were characterized 21 . The rs200562975of DPYD identified in the present study reportedly reduced enzymatic activity to less than 70% of wild-type in vitro 21 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has reported that the functional alterations of enzyme activities caused by DYPD variants were characterized 21 . The rs200562975of DPYD identified in the present study reportedly reduced enzymatic activity to less than 70% of wild-type in vitro 21 . However, none of the previous studies examined whether the DPYD variants contribute to the risk of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…To predict the enzyme-substrate specificity, both the substrate binding energy and the activation energies of the chemical steps should be considered. 69 Accordingly, we further estimated the binding affinities of the substrates of other enzymes in this family (Scheme 2) within the SkDHPase active site, using eqn (1). The binding energies of the natural substrates DHU and L-DHT are À10.8 and À15.0 kcal mol À1 , which are 2-3 times more negative than for the non-natural substrates (À5.8, À6.0, À6.8 kcal mol À1 for D-DHT, HYD, L-HYD, respectively).…”
Section: Reaction Mechanism and Substrate Specificity In Skdhpasementioning
confidence: 99%
“…Informed consent was obtained from all research participants, and the study was approved by the Tohoku Medical Megabank Organization ethics committee (permission numbers 2017-4-26, 2017-4-58, and 2017-4-090) and the Tohoku University Graduate School of Pharmaceutical Sciences ethics committee (permission number 14-08). DPYS sequence alterations were identified using Sanger sequencing according to previously described methods (Akai et al, 2015;Hishinuma et al, 2018;Hishinuma et al, 2022). The primer pairs used to detect single nucleotide variants (SNVs) in Sanger sequencing are listed in Table 2.…”
Section: Sanger Sequencingmentioning
confidence: 99%
“…In Caucasians, genetic polymorphisms in DPYD, the gene encoding DPD, contribute to individual differences in 5-FU toxicity, and the Clinical Pharmacogenetics Implementation Consortium (CPIC) guidelines have already been established for dose adjustment based on four risk variants (DPYD*2A, DPYD*13, c.2846A>T, and c.1129-5923C>G/hapB3) (Amstutz et al, 2018). However, these polymorphisms have not been identified in Asian populations (van Kuilenburg, 2004;Maekawa et al, 2007;Hishinuma et al, 2018;Yokoi et al, 2020;Hishinuma et al, 2022). Toxicity associated with 5-FU has also been observed in cancer patients with regular DPD enzymatic activity, suggesting a potential deficiency of DHPase, the second enzyme in the pyrimidine degradation pathway.…”
Section: Introductionmentioning
confidence: 99%